Implementasi Pendekatan Teaching at the Right Level (TaRL) dalam Meningkatkan Hasil Belajar Peserta Didik Kelas IV.A di SDN 47 Palembang - Hudaidah, Hudaidah; Saputri, Helen; Nopriliyanti, Khoiriah Liska (Universitas Batanghari Jambi, 2025)
This study aims to implement the Teaching at the Right Level (TaRL) approach to improve student learning outcomes in Mathematics, specifically on division operations, in class IV A of SD Negeri 47 Palembang. The research method used is Classroom Action Research (CAR), conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The results show a significant improvement in students' learning outcomes. In the pre-cycle phase, 62.5% of students had not achieved the Minimum Mastery Criteria (KKM). After implementing TaRL in the first cycle, the number of students who had not met the criteria decreased to 47%, and further dropped to 16% in the second cycle. Meanwhile, the percentage of students meeting the KKM increased from 37.5% in the pre-cycle to 53% in the first cycle and 84% in the second cycle. The implementation of the TaRL approach proved to be effective in enhancing students' understanding and learning outcomes, especially in mastering division operations.